2022
DOI: 10.1093/ajcn/nqac049
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and ultra-processed food consumption: the modifying role of participation in the Supplemental Nutrition Assistance Program (SNAP)

Abstract: Background Ultra-processed foods contribute to risks of obesity and cardiometabolic disease, and higher intakes have been observed in low-income populations in the US. Consumption of ultra-processed foods may be particularly higher among individuals experiencing food insecurity and participating in the Supplemental Nutrition Assistance Program (SNAP). Objective Using data from the 2007-2016 National Health and Nutrition Exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 63 publications
1
22
1
Order By: Relevance
“…Prior research has found that, compared to eligible non-participants, those enrolled in SNAP experience lower diet quality and may need to purchase foods that are inexpensive but are calorically dense and nutrient-poor in order to maximize their benefits ( 44 ). Notably, however, we found in this sample that SNAP participation was not associated with increased intake of SSBs, and other recent work suggests that food insecurity is not associated with increased intake of ultra-processed foods among SNAP participants ( 6 ). Policymakers should continue to consider strategies aimed to incentivize purchases of healthier foods using SNAP benefits, such as providing financial incentives for fruits and vegetables ( 45 ) or increasing the SNAP benefit size ( 46 , 47 ).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Prior research has found that, compared to eligible non-participants, those enrolled in SNAP experience lower diet quality and may need to purchase foods that are inexpensive but are calorically dense and nutrient-poor in order to maximize their benefits ( 44 ). Notably, however, we found in this sample that SNAP participation was not associated with increased intake of SSBs, and other recent work suggests that food insecurity is not associated with increased intake of ultra-processed foods among SNAP participants ( 6 ). Policymakers should continue to consider strategies aimed to incentivize purchases of healthier foods using SNAP benefits, such as providing financial incentives for fruits and vegetables ( 45 ) or increasing the SNAP benefit size ( 46 , 47 ).…”
Section: Discussioncontrasting
confidence: 68%
“…5 Overall disruption score is out of 14, with higher scores indicating greater disruption in overall diet. 6 P-values are computed from probability of direction (pd) values based on posterior samples. obscured differences observed when examining Healthy and Unhealthy sub-scores-participants experiencing FI had significantly lower scores for both types of sub-scores, suggesting they ate less of both healthy and unhealthy items.…”
Section: Diet Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that several people with food insecurity Nonetheless, it is clear that food insecurity is linked to worse-quality diets. [107][108][109] For example, based on nationally representative data, individuals participating in the Supplemental Nutrition Assistance Program (SNAP; formerly the Food Stamp Program) have an average American Heart Association dietary score of 32 out of 80 (higher scores indicate better nutrition), individuals who are incomeeligible for SNAP but not participating have an average score of 37, and individuals with higher incomes have an average score of 40. 38 Many of the challenges that create low food access likewise lead to worse nutrition.…”
Section: Mechanisms Linking Nutrition Insecurity With Cmd Throughout ...mentioning
confidence: 99%
“…In Brazil, a study in the Amazon that sought to assess food consumption and food insecurity https://doi.org/10.1017/S136898002300054X Published online by Cambridge University Press Accepted manuscript noted that fresh/minimally processed foods, such as fruits and vegetables, were considered unaffordable 49 . Using data from the 2007-2016 National Health and Nutrition Examination Survey, Leung et al 50 found that severe food insecurity was associated with higher consumption of UPF in the United States of America. Therefore, it is likely that this scenario was already present prior to the COVID-19 pandemic and may have worsened.…”
Section: Accepted Manuscriptmentioning
confidence: 99%